PENERAPAN PRINSIP TRANSPARANSI DI LINGKUNGAN PERADILAN TINGKAT PERTAMA DI YOGYAKARTA - Ishviati J Koenti (Kajian Hukum, 2018)
Transparency is the principle to open up to the right of the people to obtain correct, honest and non-discriminatory information about governance. Transparency has an important position in implementing "Good Governance", because transparency is a way to realize accountability, and encourage the effectiveness of public participation in the process of organizing the state. The Supreme Court  is obligated to provide complete on the website of the court, either the first level, the appeal or the Supreme Court.The Yogyakarta District Court is the General Court, Industrial Relations Court Corruption Act with and Class IA. The Yogyakarta District Court has a website whose content has been fulfilled under the Supreme Court Decree No. 144 / KMA / SK / VIII / 2007 concerning Information Disclosure in Court and Decree of the Chief Justice of the Supreme Court Number: 1-144 / KMA / SK / I / 2011 But in case the news has not been updated (updated) with the latest news, the latest news is the news one month ago. Religious Court of Yogyakarta, available website, but at the time of the research, is still in the repair and transfer of data, so can not be seen completeness of content and mission nisi news novelty. State Administrative Court   Yogyakarta already has a website whose content has been filled and fulfill what is stipulated in the Decision Letter of the Supreme Court of the Republic of Indonesia.Keywords: transparency principle, court, supreme court decree